Corporate Strategy (Remastered) II: A Fieldbook Implementing High Performance Strategy and Leadership - Hunter, Paul (Routledge, 2021)
Since the onset of the Fourth Industrial Revolution numerous corporations have found that traditional ‘strategic planning’ is ineffectual in responding to, or capitalising on, unforeseen or unexpected change. In recognition of this and associated symptoms of inertia, bankruptcy or worse, this fieldbook was written for the purpose of guiding strategy practitioners through their intended or unintended journey into the future by providing meaningful strategy practices that enable responses to disruption and more importantly, better strategy practices overall. With a focus on strategy practice (‘doing’ strategy), this book represents a ‘how-to’ of Third Wave Strategy as defined in detail in the introductory book Corporate Strategy (Remastered) I. In addition to a description of methods that contribute to the philosophy of Third Wave Strategy, readers will witness the experiences of a virtual illustrative company that is travailing the same journey of organisational transformation and renewal that the methodologies described in this book also seek to address. The overall value of the book, therefore, is its ability to relate theory to practice in a factual and experiential format. A key part of the use of the virtual case study based on the illustrative Third Wave Industries (T-wI) Corporation is the blending of the system and process mechanisms that are a part of Third Wave Strategy and its framework, the strategy tools and techniques that are drawn from new and existing strategy practice and the soft issues that are represented by the human responses to change, as well as the management of change enacted in a corporate environment.